Improvement of the Early-Age Compressive Strength, Water Permeability, and Sulfuric Acid Resistance of Scoria-Based Mortars/Concrete Using Limestone Filler - Aref Al-Swaidani; Andraos Soud; Amina Hammami (Advances in Materials Science and Engineering)
Natural pozzolan is being widely used as cement replacement. Despite the economic, ecological, and technical benefits of its adding, it is often associated with shortcomings such as the need of moist-curing for longer time and a lower early strength. This study is an attempt to investigate the effect of adding limestone filler on the compressive strength and durability of mortars/concrete containing scoria. Sixteen types of binders with different replacement levels of scoria (0, 10, 20, and 30%) and limestone (0, 5, 10, and 15%) were prepared. The development of the compressive strength of mortar/concrete specimens was investigated after 2, 7, 28, and 90 days’ curing. In addition, the acid resistance of the 28 days’ cured mortars was evaluated after 90 days’ exposure to 5% H2SO4. Concrete permeability was also evaluated after 2, 7, 28, and 90 days’ curing. Test results revealed that there was an increase in the early-age compressive strength and a decrease in water penetration depths with adding limestone filler. Contrary to expectation, the best acid resistance to 5% H2SO4 solution was noted in the mortars containing 15% limestone. Based on the results obtained, an empirical equation was derived to predict the compressive strength of mortars.